Pengaruh Net Profit Margin, Return On Asset, Dan Return On Equity Terhadap Financial Distress Pada Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020 - Maria Kaok; Nur Aliyah Syairah Akbar (Musamus Accounting Journal, 2023)
This study aims to determine the effect of Net Profit Margin, Return On Assets, and Return On Equity on Financial Distress in Food & Beverage Companies Listed on the Indonesia Stock Exchange in 2018-2020. The research method used is quantitative research. The population used was 26 companies with purposive sampling technique so that a sample of 50 data was obtained. The data used in this study is secondary data in the form of company financial statements. The financial distress calculation method uses the Zmijewski method where if the calculation results are positive, then the company is considered unhealthy and vice versa. The analytical tool used in this research is SPSS version 26. The results of this study indicate that the net profit margin (NPM) variable has no partial effect on financial distress in food & beverage companies listed on the Indonesia Stock Exchange in 2018-2020. The variable return on assets (ROA) has a partial effect on financial distress in food & beverage companies listed on the Indonesia Stock Exchange in 2018-2020. The return on equity (ROE) variable has a partial effect on financial distress in food & beverage companies listed on the Indonesia Stock Exchange in 2018-2020. The variables net profit margin (NPM), return on assets (ROA), and return on equity (ROE) simultaneously affect financial distress in food & beverage companies listed on the Indonesia Stock Exchange in 2018-2020.